Duodenal mucosal reductase in wild-type and Hfe knockout mice on iron adequate, iron deficient, and iron rich feeding. Issue 4 (1st April 2003) - Simpson, R J; Debnam, E; Beaumont, N; Bahram, S; Schümann, K; Srai, S K S
Abstract : Background: Genetic haemochromatosis is a common hereditary iron loading disorder in humans. The disease is associated with loss of function mutations in the HFE gene. This is thought to change iron stores via increased iron absorption. Aims: In this study we investigated how adaptation of mucosal reductase activity is engaged in this process and how the changes compare with adaptation seen when an iron deficient diet is fed. Methods: Duodenal mucosal surface reductase was measured with nitroblue tetrazolium in age matched groups of male Hfe knockout mice (Hfe) and wild- type mice fed a purified diet containing normal (iron adequate), high (iron rich), or low (iron deficient) iron concentrations. Results: Reductase activity increased when mice were fed an iron deficient diet and decreased when they were fed an iron rich diet. Total villus activity, as measured by the average area under the activity curve along the crypt-villus axis, was increased 2.8–2.9-fold by iron deficiency in both genotypes. Approximately half of this difference was attributable to the significantly increased length of the villi in mice on an iron deficient diet (p<0.05). Hfe knockout did not affect villus length but increased mucosal reductase activity near the villus tips. Similar increases (1.3–1.6-fold) were seen on all diets but the increase was significant for iron deficient and iron loaded diets only (p<0.05). Conclusion: Hfe gene product and dietary iron downregulate villus reductase activity in mice.